Cancer epidemiology and control in peninsular and island South-East Asia - past, present and future - Moore, M.A.; Ab Manan, A.; Chow, K.Y.; Cornain, S.F.; Devi, C.R.B.; Triningsih, F.X.E.; Laudico, A.; Mapua, C.A.; Mirasol-Lumague, M.R.; Noorwati, S.; Nyunt, K.; Othman, N.H.; et al. (2010)
Malaysia, Brunei, Singapore, Indonesia, East Timor and the Philippines constitute peninsular and island South-East Asia. For reasons of largely shared ethnicity, with Chinese elements added to the basic Austromalaysian populations, as well as geographical contiguity, they can be usefully grouped together for studies of chronic disease prevalence and underlying risk factors. The fact of problems are shared in common, particularly regarding increasing cancer rates, underlines the necessity for a coordinated approach to research and development of control measures. To provide a knowledge base, the present review of available data for cancer registration, epidemiology and control was conducted. The most prevalent cancer site in males is the lung, followed by the liver, colon or the prostate in the majority of cases, while breast and cervical cancers predominate in most female populations. However, there are interesting differences among the racial groups, particularly regarding the stomach. General tendencies for increase in adenocarcinomas but decrease in squamous cell carcinomas and gastric cancer, point to change in environmental influence over time. Variation in risk factors depends to some extent on the level of economic development but overall the countries of the region face similar challenges in achieving effective cancer control. A major task is persuading the general populace of the efficacy of early detection and clinical treatment.